2020
DOI: 10.1021/acs.est.0c03254
|View full text |Cite
|
Sign up to set email alerts
|

Suspended Particle–Water Interactions Increase Dissolved 137Cs Activities in the Nearshore Seawater during Typhoon Hagibis

Abstract: Distributions of 137 Cs in dissolved and particulate phases of the downstream reaches of seven rivers and adjacent nearshore and offshore waters as far as ∼60 km south of the Fukushima Dai-ichi nuclear power plant (FDNPP) were studied during the high-river-flow period (June−September 2019) and during the period of October 2019 after typhoon Hagibis. Dissolved 137 Cs activities in nearshore water were higher than those in rivers and offshore waters, and this distribution was more intensified after the typhoon,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…That is, it is reasonable to expect that a considerable portion of the radiocesium was in particulate form at the inshore stations, whereas it was mainly in dissolved form at the offshore stations. The reason for the presence of particulate radiocesium at the inshore stations is that, as mentioned above, the large amount of river runoff stirred up and resuspended radiocesium that had already accumulated on the shallow sea bottom near the river mouths (Charette et al 2013; Otosaka and Kobayashi 2013; Otosaka and Kato 2014; Buesseler et al 2015; Sanial et al 2017; Uchiyama et al 2017; Takata et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, it is reasonable to expect that a considerable portion of the radiocesium was in particulate form at the inshore stations, whereas it was mainly in dissolved form at the offshore stations. The reason for the presence of particulate radiocesium at the inshore stations is that, as mentioned above, the large amount of river runoff stirred up and resuspended radiocesium that had already accumulated on the shallow sea bottom near the river mouths (Charette et al 2013; Otosaka and Kobayashi 2013; Otosaka and Kato 2014; Buesseler et al 2015; Sanial et al 2017; Uchiyama et al 2017; Takata et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The probability of this type of discharge will increase if a large runoff event occurs just before a water‐sampling survey, which was the case in this study (as will be discussed in the subsection of the Precipitation and river discharge section). Moreover, it is plausible that the large amount of river runoff stirred up and resuspended radiocesium that had already accumulated on the shallow sea bottom near the river mouths; high levels of radiocesium had been deposited onto seabed sediments in coastal areas (Charette et al 2013; Otosaka and Kobayashi 2013; Otosaka and Kato 2014; Buesseler et al 2015; Sanial et al 2017; Uchiyama et al 2017; Takata et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anomalies were observed along a cliff in these at areas, 5 km from the river mouth. Radiocesium is transported to sea in combination with ne particles smaller than 10 mm 9,15 . The distribution characteristics in the contour maps showed that such ne particles owing along the rivers were carried by approximately 5 km from the river mouth and accumulated in the hollow of a cliff.…”
Section: Characteristics Of Cs Distributionmentioning
confidence: 99%
“…Otosaka (2017) estimated that > 43% of 137 Cs in the surface sediment around the FDNPP was transported to deeper sediment layers via vertical mixing of sediments from March 2011 to the end of 2015 8 . Moreover, radiocesium, which ows from rivers to seas, increases during ooding events, such as typhoons 9 . These evaluation values are based on limited monitoring data, such as grab sampling and short core sampling data of several dozens.…”
Section: Introductionmentioning
confidence: 99%